Chemotherapeutic properties and side-effects associated with the clinical practice of terpene alkaloids: paclitaxel, docetaxel, and cabazitaxel - Sousa-Pimenta, Mário; Estevinho, Letícia M.; Szopa, Agnieszka; Basit, Mahnoor; Khan, Khushbukhat; Armaghan, Muhammad; Ibrayeva, Manshuk; Sönmez Gürer, Eda; Calina, Daniela; Hano, Christophe; Sharifi-Rad, Javad (Frontiers in Pharmacology, 2023)
The Uncontrolled cell division leads to cancer. Over the years, many biological and synthetic agents have been explored and tested in attempts to halt the spread of cancer and/or to cure it. Currently, several natural compounds have and are being considered in this regard. For example, paclitaxel is a potent anticancer drug that originates from the tree Taxus brevifolia. Paclitaxel has several derivates, namely docetaxel and cabazitaxel. The paclitaxel and the derivatives work by disrupting microtubule assembling dynamics and inducing cell cycle arrest at the G2/M phase of the cell cycle, ultimately triggering apoptosis. Such features have helped to establish paclitaxel as an authoritative therapeutic compound against neoplastic disorders. Once compound (hemi)synthesis attained completion, this drug was approved for usage either alone or in a combination with other agents to treat solid tumors. In this review, we discuss the course of action of paclitaxel and its derivatives, their various formulations, and cancer-resistant molecular pathways, along with their possible hazards and other indications. In addition, the role of paclitaxel in hematological malignancies is explored, and potential limitations in the therapeutic use of paclitaxel at the clinical level are examined. Furthermore, the immunomodulatory potential of paclitaxel is also explored. The drug also causes increased Antigen presentation which helps in the treatment of cancer patients. Moreover, the role of Taxanes and their derivatives with respect to all hallmarks of cancer has also been discussed in this manuscript. On the whole, Taxol derivatives are effective in inducing apoptosis by acting as an anti-mitotic therapeutic agent. Such characteristics make them a potent medication in the treatment of neoplastic disorders. This has been backed up by the summary of various clinical trials mentioning the dose of Taxanes and the type of cancer they are effective for. The various formulations of PTX and with similar pharmokinetic profiles have helped in the establishment of PTX as a microtubule disassembling agent.